Effects of male telomeres on probability of paternity in sand lizards. (22nd August 2018) - Pauliny, Angela; Miller, Emily; Rollings, Nicky; Wapstra, Erik; Blomqvist, Donald; Friesen, Chris R.; Olsson, Mats
Abstract : Standardized swim-up trials are used in in vitro fertilization clinics to select particularly motile spermatozoa in order to increase the probability of a successful fertilization. Such trials demonstrate that sperm with longer telomeres have higher motility and lower levels of DNA damage. Regardless of whether sperm motility, and successful swim-up to fertilization sites, is a direct or correlational effect of telomere length or DNA damage, covariation between telomere length and sperm performance predicts a relationship between telomere length and probability of paternity in sperm competition, a prediction that for ethical reasons cannot be tested on humans. Here, we test this prediction in sand lizards ( Lacerta agilis ) using experimental data from twice-mated females in a laboratory population, and telomere length in blood from the participating lizards. Female identity influenced paternity (while the mechanism was not identified), while relatively longer male telomeres predicted higher probability of paternity. We discuss potential mechanisms underpinning this result.